Association of childhood tracheomalacia with bronchiectasis: a case–control study. Issue 6 (14th October 2021) - Thomas, Rahul; Chang, Anne; Masters, Ian Brent; Grimwood, Keith; Marchant, Julie; Yerkovich, Stephanie; Chatfield, Mark; O'Brien, Christopher; Goyal, Vikas
Abstract : Objective: Children with tracheomalacia can develop chronic lower airway infection and neutrophilic inflammation. It is plausible children with tracheomalacia are at increased risk of developing bronchiectasis. We hypothesised that compared with controls, tracheomalacia in children is associated with bronchiectasis. Design: Single-centre, case–control study. Setting and patients: 45 children with chest high-resolution CT (c-HRCT) confirmed bronchiectasis (cases) and enrolled in the Australian Bronchiectasis Registry were selected randomly from Queensland, and 90 unmatched children without chronic respiratory symptoms or radiographic evidence of bronchiectasis (disease controls). Cases and controls had flexible bronchoscopy performed for clinical reasons within 4 weeks of their c-HRCT. Interventions: The bronchoscopy videos were reviewed in a blinded manner for: (a) any tracheomalacia (any shape deformity of the trachea at end-expiration) and (b) tracheomalacia defined by the European Respiratory Society (ERS) statement (>50% expiratory reduction in the cross-sectional luminal area). Main outcome measures and results: Cases were younger (median age=2.6 years, IQR 1.5–4.1) than controls (7.8 years, IQR 3.4–12.8), but well-balanced for sex (56% and 52% male, respectively). Using multivariable analysis (adjusted for age), the presence of any tracheomalacia was significantly associated with bronchiectasis (adjusted OR (ORadj )=13.2, 95% CI 3.2 to 55), while that for ERS-defined tracheomalacia further increased this risk (ORadj =24.4, 95% CI 3.4 to infinity). Conclusion: Bronchoscopic-defined tracheomalacia is associated with childhood bronchiectasis. While causality cannot be inferred, children with tracheomalacia should be monitored for chronic (>4 weeks) wet cough, the most common symptom of bronchiectasis, which if present should be treated and then investigated if the cough persists or is recurrent. Abstract : In this case-control study, Thomas et al identify a significant association between tracheomalacia and bronchiectasis (adjusted Odds Ratio 13) which should guide the investigation of children with tracheomalacia and chronic cough.